Indonesian Volleyball Association (PBVSI) on Increasing Athlete's Achievement in Tegal Regency - Warsito, Hadi; Sulaiman, Sulaiman; Irawan, Fajar Awang (Journal of Physical Education and Sports, 2019)
The objectives to be achieved through this research are: reviewing, analyzing and concluding planning, organizing, actuating, and controlling systems in the PBVSI management of Tegal Regency. This research is qualitative research with descriptive analysis approach, while the data collection method used by researchers is observation, interviews, and documentation. The conclusions of this study are PBVSI Tegal Regency has very good planning, because in its planning found five planning criteria in sports organizations, namely: clear who worked, what is done, when done, where it is done or carried out, and clearly how it was implemented. Besides, PBVSI Tegal Regency has carried out joint planning which is planned and decided together during deliberations and work meetings. Planning that is designed is not only a formality, because planning that is designed is mostly carried out; PBVSI Tegal Regency already has good organization, because it only fulfills four of the five criteria in organizing sports organizations namely have a complete manager, mechanism of activity, job description, and there are routine activities that are carried out (coaching activities, championships, meetings), but there has been no discussion of a meeting or deliberation at the beginning of the year. All management elements cooperate in completing tasks following the competencies in their respective fields; Implementation in coaching management at PBVSI in Tegal Regency is included in a good category, because it only finds three criteria from four categories in the implementation of sports organizations namely implement the program, program implementation, complete 5M (man, money, method materials, and machine). Because the implementation has not been able to obtain maximum achievements; Supervision in PBVSI management in Tegal Regency is included in the sufficient category because it only meets two of the four categories, namely reporting and evaluation, but there is no supervision and monitoring.